Penfigoide de membrana mucosa asociado a carcinoma pulmonar ¿penfigoide paraneoplásico? - Urbano del Valle, Samuel (2021)
Mucous membrane pemphigoid is an autoimmune disease that affects different layers from mucosa and skin, characterized by polymorphic vesicular-bullous lesions, presenting variable combinations of oral, ocular, skin, genital, nasopharyngeal, esophageal, and laryngeal lesions. Its relationship to malignant neoplasms is poorly understood and remains controversial. This article describes the multidisciplinary management of a 46-year-old patient who developed mucous membrane pemphigoid at the oral cavity level. This pathology was associated with lung carcinoma, and later presented multiorgan alterations, for which a treatment was carried out with the specialties of dermatology, internal medicine, general surgery, ophthalmology, stomatology, oral and maxillofacial surgery, said treatment was carried out in stages and lasted for approximately 2 months, achieving the resolution about lesions that patient presented. We believe that a door opens for future research confirming the relationship between mucous membrane pemphigoid and lung carcinoma.